(untitled) (Gestión y Gerencia, 2025)
Organizational climate represents a key factor affecting employee satisfaction and commitment, being essential for the long-term sustainability and competitiveness of organizations. This refers to shared perceptions about their work environment, including leadership, communication, and organizational culture. This is evident in the structure of the organizational climate, which manifests both explicit elements, such as work hierarchies and resource availability, and implicit components, including institutional values ​​and the quality of interpersonal relationships. All of these interact dynamically and shape the daily experience of workers within the organization. This study was based on a qualitative research methodology with systematic search strategies through digital repositories: Scielo, Science Research, Scopus, Elsevier, ScienceDirect, and Google Scholar; these allowed us to identify relevant literature, along with the use of specifically defined inclusion and exclusion criteria to ensure the relevance and quality of the selected studies. It is concluded that continuous climate assessment is an important resource for adapting to change. This involves the periodic application of validated instruments and rigorous feedback analysis to adapt design optimization and change management strategies. This can be leveraged as an important resource for adapting to internal and external changes, promoting a culture of recognition that motivates employees. It also employs strategies that include design optimization, change management, and the implementation of recognition programs.